SHOULD GARUDA INDONESIA JOIN THREE MAJOR AIRLINES ALLIANCES : STAR ALLIANCE, ONE WORLD AND SKY TEAM - Basri Fahriza (Institut Transportasi dan Logistik Trisakti, 2016)
This research was conducting in 2005 to analyse the need of Garuda Indonesia to join airlines alliance. Situational analysis is conducted illustrating where Garuda Indonesia in 2005. In the external environment, Garuda can look forward to and hence prepare for the ASEAN open skies to commence operation as soon as this decade. At the core of the report following the Garuda SWOT analysis (indicating the strengths, weaknesses, opportunities and strengths), the strategic plan, and Garuda’s ambition is identified as being to be the strongest carrier in Asia Pacific within next five years. The strategic solution is provides two alternatives, to join an alliance group- supporting material further emphasises the importance of this move, and the other option is to not join an alliance and have the Indonesian carrier rather capitalise on seeking and/or maintaining current bilateral agreements with other carriers.